2005
DOI: 10.2164/jandrol.04171
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in a Bearded Woman

Abstract: A 61-year-old woman with no past medical history was admitted with nonketotic hyperosmolar state that was complicated by seizures. At presentation, her serum glucose was 800 mg/dL with negative ketones. Glycosylated hemoglobin (HbA1c) was 14.1%. The patient was started on intravenous insulin and fluids. Serum insulin levels were not measured since the patient was already started on an insulin drip. She was also noted to have virilization. She had normal menarche, regular menses until menopause, and had deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The coexistence of luteomas with such conditions as polycystic ovarian syndrome and diabetes has been well established (7,19,20). Recurrence of luteomas is rare (7); however, there have been at least 5 reports of recurrent virilization in subsequent pregnancies (18).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The coexistence of luteomas with such conditions as polycystic ovarian syndrome and diabetes has been well established (7,19,20). Recurrence of luteomas is rare (7); however, there have been at least 5 reports of recurrent virilization in subsequent pregnancies (18).…”
Section: Epidemiologymentioning
confidence: 99%
“…Four case reports exemplify the following difference: a 61-year-old diabetic who had virilization and difficulty with insulin resistance and poor glycemic control (20); a 65-year-old with endometrial adenocarcinoma who was found to have an adnexal mass during surgery defined as a "stromal luteoma" (28); a 63-year-old Japanese woman with a stromal luteoma, nodular hyperthecosis, and atypical endometrial hyperplasia (26); and a 65-year-old with postmenopausal bleeding secondary to endometrial hyperplasia (29). These presentations demonstrate an association between endometrial hyperplasia and stromal luteomas.…”
Section: Differential Diagnosismentioning
confidence: 99%